2023
DOI: 10.3390/agronomy13081976
|View full text |Cite
|
Sign up to set email alerts
|

Agroclimatic and Phytosanitary Events and Emerging Technologies for Their Identification in Avocado Crops: A Systematic Literature Review

Tomas Ramirez-Guerrero,
Maria Isabel Hernandez-Perez,
Marta S. Tabares
et al.

Abstract: Avocado is one of the most commercialized and profitable fruits in the international market. Its cultivation and production are centered in countries characterized by tropical and subtropical climatic conditions, many of them with emerging economies. Moreover, the use of technology is key to agricultural production improvement strategies. Using avocado crop data to forecast the potential impacts of biotic and abiotic factors, combined with smart farming technologies, growers can apply measures during a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…As mentioned above, these technologies, which are often referred to as "digital agriculture" or "precision-smart farming" are the foundation for a new, more productive, and sustainable agriculture. So, the purpose of the mapping exercise presented here was to facilitate a description of the evidence base so that a subset of keywords from the maps of Figures 1-4 could be identified in the following contributed papers [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, these technologies, which are often referred to as "digital agriculture" or "precision-smart farming" are the foundation for a new, more productive, and sustainable agriculture. So, the purpose of the mapping exercise presented here was to facilitate a description of the evidence base so that a subset of keywords from the maps of Figures 1-4 could be identified in the following contributed papers [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…In this research, authors monitored UAV technologies such as UAV cameras for patchy creeping perennial weeds in field experiments and concluded that future improvements in UAV-based camera technologies could monitor important weeds in the field and effectively control them. In the third article, Ramirez-Guerrero et al [15] reported that emerging technologies in agriculture such as 4IR technologies could help farmers to detect pests and diseases. Moreover, the author's primary focus was emerging technologies for avocado crops such as data collection techniques and image devices.…”
Section: Discussionmentioning
confidence: 99%
“…Avocado is produced mainly in Mexico (33%), the Dominican Republic (10.5%), Peru (7.8%), Indonesia (5.7%), and Colombia (5.1%) [29], where investment for planting and harvesting has increased in recent years [30]. In Europe, avocado consumption per capita increased by approximately 180% between 2018 and 2020, projecting these values to a more significant increase by 2025 [31].…”
Section: Introductionmentioning
confidence: 99%
“…Such knowledge facilitates the selection of prioritized genotypes for conservation strategies and the development of new varieties with improved fruit quality and maturation precocity. By leveraging genetic diversity, researchers can optimize avocado cultivation, ensuring sustainable and profitable fruit production [13].…”
Section: Introductionmentioning
confidence: 99%